2014
DOI: 10.1080/02791072.2014.901587
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Abstinence or Continued Drug Use Among Methadone Maintenance Patients and Their Relation to Treatment Retention

Abstract: The efficacy and effectiveness of methadone maintenance treatment (MMT) in the medical management of opioid addiction has been well-established, but treatment outcomes are compromised by the continued use of licit and illicit drugs during MMT. The present study examined the relationship between in-treatment illicit drug use and retention and dropout of 604 MMT patients in Washington, D.C. Sixty-eight percent of patients did not test positive for an unprescribed drug during the study period. Of patients who tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 73 publications
2
69
0
Order By: Relevance
“…In this study, we examined satisfaction with methadone in a subgroup of heroin-dependent patients of great interest to both clinicians and researchers: patients who compulsively use heroin and/or nonopioid substances during MMT. 1,[3][4][5][6][7] We were also able to identify 5 factors that were independently associated with SASMAT-METHER assessments in patients with current SUD: desire for a downward adjustment of methadone dose, patient perceived influence on methadone dose changes, days of heroin or cocaine use during last month, and years of education. Unexpectedly, we found that the desire to adjust the methadone dose downward was significantly associated with all dimensions of satisfaction with methadone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examined satisfaction with methadone in a subgroup of heroin-dependent patients of great interest to both clinicians and researchers: patients who compulsively use heroin and/or nonopioid substances during MMT. 1,[3][4][5][6][7] We were also able to identify 5 factors that were independently associated with SASMAT-METHER assessments in patients with current SUD: desire for a downward adjustment of methadone dose, patient perceived influence on methadone dose changes, days of heroin or cocaine use during last month, and years of education. Unexpectedly, we found that the desire to adjust the methadone dose downward was significantly associated with all dimensions of satisfaction with methadone.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5] Interruption of the compulsive use of nonopioid substances is also often a secondary therapeutic goal of MMT. 1,[3][4][5] The use of certain nonopioid substances, including benzodiazepines 6 and cocaine, 3,7 has been found to be associated with heroin use during MMT. This finding suggests that methadone-induced changes in heroin addiction through selective substitution and blockage of the effects of heroin 8,9 could also lead to changes in the use of nonopioid substances.…”
mentioning
confidence: 99%
“…This polysubstance use could reflect an association between behavioral disinhibition and a continuum of addiction defined primarily in terms of polysubstance involvement (Conway, Kane, Ball, Poling, & Rounsaville, 2003). In this context, it is not surprising to observe high rates for use of substances other than opiates among MMT patients, and addictive behaviors persisting after treatment initiation (Clarke et al, 2001;Moitra et al, 2013;Richter et al, 2001;SAMHSA, 2012;White et al, 2014). While not appearing to be significant factors of MMT discontinuation, these behaviors may suggest that many patients spend a considerable proportion of recovery time taking other substances and are likely to be exposed to many of the health risks inherent in chronic substance use (Kidorf et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who initiate MMT are likely to concurrently use psychoactive substances other than opiates (Clarke, Stein, McGarry, & Gogineni, 2001;Moitra, Anderson, & Stein, 2013;Richter, Gibson, Ahluwalia, & Schmelzle, 2001;White et al, 2014), in particular cannabis, which is also the most-used illicit substance in industrialized countries (Compton, Thomas, Conway, & Colliver, 2005;Kidorf, Neufeld, King, Clark, & Brooner, 2007). Research results are mixed regarding the effect of MMT on cannabis use, and measurements of the drug's use during treatment are infrequently and irregularly reported in the literature (Amato et al, 2005;SAMHSA, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is possible that the presence of medical or psychiatric comorbidities plays a role in a patient's illicit polysubstance use (24). However, an attempt to control for some comorbidities was indirectly made, as all participants currently prescribed opioids were excluded from the final analysis.…”
Section: Discussionmentioning
confidence: 99%